2020
DOI: 10.3389/fpubh.2020.00434
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Lifestyle-Integrated Physical Activity Intervention to Enhance Physical Activity, Positive Family Communication, and Perceived Health in Deprived Families: A Cluster Randomized Controlled Trial

Abstract: Background: Zero-time exercise (ZTEx) is an approach integrating simple strength-and stamina-enhancing physical activity into daily life. The study evaluated the effectiveness of a community-based lifestyle-integrated physical activity intervention using ZTEx to enhance participants' physical activity, family communication, perceived health and happiness, and family harmony. Methods: A parallel group, cluster randomized controlled trial was conducted in a sample of 673 participants from eight Integrated Family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Family harmony was also assessed by asking, “How harmonious do you think your family is?” on a scale of 0 (very unharmonious) to 10 (very harmonious). We have used the three family well-being questions in previous papers [ 23–26 ], and have also shown that the family happiness question is a reliable and valid measurement tool [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Family harmony was also assessed by asking, “How harmonious do you think your family is?” on a scale of 0 (very unharmonious) to 10 (very harmonious). We have used the three family well-being questions in previous papers [ 23–26 ], and have also shown that the family happiness question is a reliable and valid measurement tool [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, because validated questionnaires were unavailable, we self-developed our outcomebased questions to assess the probationers' practices in relation to doing simple strength-and stamina-enhancing physical activity by themselves and with their family members and expressing appreciation to family members. The acceptability and applicability of these questions were shown in our previous studies with similar designs (Ho et al, 2020;Lai et al, 2020). Second, we were unable to assess the accumulated duration of physical activity objectively; we only measured the selfreported number of days engaged in physical activity.…”
Section: Discussionmentioning
confidence: 97%
“…A meta-analysis of 51 positive psychology interventions concluded that positive psychology interventions significantly enhanced psychosocial well-being ( Sin and Lyubomirsky, 2009 ). “Praise and Gratitude” is a combination of the expression of thankfulness and an emotional sense of appreciation ( Emmons and McCullough, 2003 ; Peterson and Seligman, 2004 ), which are among the easiest and most commonly applied positive psychology themes into daily life to enhance personal and family well-being ( Ho et al, 2019 ; Lai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations